THE EFFECTIVENESS OF PRE-PRACTICE PREPARATION PROGRAM IN PRACTICUM OF ADULT AND GERONTOLOGICAL NURSING II IN NEW NORMAL ERA ON KNOWLEDGE, PRACTICAL SKILLS AND CONFIDENCE, IN THE THIRD YEAR NURSING STUDENTS - Jaipang, Chulaluk; Jeranukul, Araya (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
This mixed-methods research study aimed to investigate the effectiveness of the pre-practice preparation program on knowledge, practical skills, and confidence, as well as to explore the experiences of third-year nursing students in the practicum in adult and gerontological nursing II during the new normal era. The participants consisted of 89 third-year nursing students enrolled in this program and twenty-five nursing students engaged in group discussions and underwent an in-depth interview process. The research instruments included the pre-practice preparation program, questionnaires on personal data, knowledge, practical skills, and confidence, as well as group discussion and in-depth interview questions. Quantitative data were collected before qualitative data. Descriptive statistics, one-way repeated measures ANOVA, the Friedman test and the paired t-test were employed to analyze the data. The results showed that average scores for knowledge and confidence were significantly higher immediately after and 2 months after the program compared to the beginning (p < .05). Nursing practice skills immediately after the program were also significantly higher than 2 months after the program (p < .05). The experience of participating in the pre-practice preparation program has two main points: 1) the program had promotes practical learning including enhancing knowledge, understanding, and confidence; and 2) the program had limitations, including limited time, non-continuous practice, the inability to observe changes in patients, and the inability to provide online experiences for some skills. In conclusion, the pre-practice preparation program had demonstrated its efficacy in improving nursing students’ knowledge, practical skills, and confidence in the new normal era.